Production, Biosynthesis, and Commercial Applications of Fatty Acids From Oleaginous Fungi - Zhang, Xin-Yue; Li, Bing; Huang, Bei-Chen; Wang, Feng-Biao; Zhang, Yue-Qi; Zhao, Shao-Geng; Li, Min; Wang, Hai-Ying; Yu, Xin-Jun; Liu, Xiao-Yan; Jiang, Jing; Wang, Zhi-Peng (Frontiers in Nutrition, 2022)
Oleaginous fungi (including fungus-like protists) are attractive in lipid production due to their short growth cycle, large biomass and high yield of lipids. Some typical oleaginous fungi including Galactomyces geotrichum, Thraustochytrids, Mortierella isabellina, and Mucor circinelloides, have been well studied for the ability to accumulate fatty acids with commercial application. Here, we review recent progress towards fermentation, extraction, of fungal fatty acids. To reduce cost of the fatty acids, fatty acid productions from raw materials were also summarized. Then, the synthesis mechanism of fatty acids was introduced. We also review recent studies of the metabolic engineering strategies have been developed as efficient tools in oleaginous fungi to overcome the biochemical limit and to improve production efficiency of the special fatty acids. It also can be predictable that metabolic engineering can further enhance biosynthesis of fatty acids and change the storage mode of fatty acids.